MCT4 inhibition attenuates inflammatory response to Mycobacterium avium paratuberculosis infection and restores intestinal epithelial integrity in vitro - Alhendi, Ala’; Naser, Saleh A. (Frontiers in Immunology, 2025)
IntroductionMycobacterium avium paratuberculosis (MAP) plays a significant role in Crohn’s disease (CD). Monocarboxylate transporter 4 (MCT4) is a proton-coupled symporter of lactate that facilitates the inflammatory shift in macrophages and increases their reliance on glycolysis. MCT4 is also involved in the negative regulation of intestinal epithelial barrier function.MethodsIn this in vitro study, we examined the role of MCT4 in macrophages and its effect on intestinal epithelial homeostasis during MAP infection. We used cultured THP-1 macrophages infected with a clinical strain of MAP (UCF4) as well as intestinal cell lines, Caco-2 and HT-29. MCT4 was inhibited using α-cyano-4-hydroxycinnamic acid (CHCα).ResultsInfection of THP-1 cells with MAP upregulated MCT4 expression (2 folds) and resulted in a significant increase in lactate export (1.3 folds), TNFα (13.8 folds), and IL-6 (1.3) via TLR2 activation. Consequently, intestinal damage markers were also upregulated, including MUC2 (2.5 folds), NOX-1 (2 folds), SERPINE1 (2.1 folds), IL-6 (1.6 folds), and CLDN2 (1.4 folds). Inhibition of MCT4 during MAP infection with CHCα significantly reduced TNF-α and IL-6 levels. This effect on macrophages restored baseline oxidative status and mucin production in HT-29 intestinal cells. Moreover, MCT4 inhibition in a MAP-infected THP-1-Caco-2 co-culture system restored IL-6 and SERPINE1 to normal levels and enhanced tight junction protein, TJP1 (ZO-1), expression.ConclusionCollectively, this study revealed the significant role of MCT4 in CD pathophysiology during MAP infection and highlighted MCT4 as a potential therapeutic target for CD treatment.